MODEL PENGEMBANGAN PEMBELAJARAN BERBASIS MULTIMEDIA - Rahmawati; Muh. Rapi (Jurnal Pendidikan Kreatif, 2023)
Multimedia is a learning medium that combines several learning media in the learning process. Multimedia is expected to be able to contribute more in increasing the achievement of learning objectives. several multimedia learning media including the first model, namely the interactive communication model, namely the design method. as an animation maker), simulation models (students are given the freedom to imitate things exhibited by the computer), and game models (commuters are used as games in learning); The second APPED model is the development of multimedia products in the form of an offline Interactive CD while the procedural includes analysis and original research, design, production, evaluation and socialization, and the third is the Experiential Learning Cycle, namely learning multimedia mixed interactive media through animation, interactive media through decapitation materials are shorter, using communication that is easy for students to understand and interactive media that can improve student learning outcomes.